In-Group Loyalty and the Punishment of Corruption - Solaz, Hector; de Geus, Roosmarijn; de Vries, Catherine (Sage Journals, 2019)
This study suggests that in-group loyalty, defined as the degree to which people favor their own group over others, undermines the punishment of corruption. We present evidence from two studies. First, we utilize a real-world corruption scandal involving the ruling party in Spain that broke during survey fieldwork. People exposed to the scandal withhold support from the incumbent, but in-group loyalty based on partisanship weakens this effect. Second, we explore in-group loyalty beyond partisanship through laboratory experiments. These experiments artificially induce group identities, randomly assign the group identity of candidates and shut down any instrumental benefits of in-group loyalty. The experimental evidence suggests that people support corrupt candidates as long as they share a group identity and are willing to sacrifice material payoffs to do so. Our findings have important implications. Most importantly perhaps, they suggest that candidates can get away with corruption by engaging in identity politics.
Keywords: 63 Sociología; ODS 16 - Paz, justicia e instituciones sólidas; corruption and patronage; elections; public opinion; and voting behavior; European politics